RETRACTED: Crop leaves high-resolution images analysis and segmentation by a convolutional neural network under small sampling condition - Tokarev Kirill; Lebed Nikita; Nekhoroshev Dmitriy; Popov Alexander; Klimenko Vladimir (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001